Chain mediating effect of perceived organizational support and resilience on workplace violence and perceived professional identity of emergency nurses: a structural equation model analysis - Junjie Tao; Yuchuan Wang; Meng Chen; Zhenlong Yan; Ping Huang (BMC Nursing)
Abstract Background Emergency nurses face exceptionally high rates of workplace violence, posing a significant threat to their perceived professional identity. While perceived organizational support and resilience are recognized as potential protective factors, the specific pathways particularly their chain mediating roles linking workplace violence to diminished perceived professional identity among this high-risk group remain inadequately explored and lack empirical validation within the Chinese healthcare context. Methods A convenience sample of 1,804 emergency nurses was recruited from 13 cities across Jiangsu Province, China, during January-March 2024. Participants completed: (1) A Sociodemographic Questionnaire, (2) Workplace Violence Scale, (3) Nurse Organizational Support Scale, (4) Medical Staff Resilience Scale, and (5) Nurse Professional Identity Scale. Structural equation modeling examined the chain mediation of perceived organizational support and resilience on the workplace violence and perceived professional identity among emergency nurses. Results The results of correlation analysis showed that workplace violence was negatively correlated with perceived organizational support (r=-0.308, P < 0.01), resilience (r=-0.403, P < 0.01) and perceived professional identity (r=-0.454, P < 0.01); perceived organizational support was positively correlated to resilience (r = 0.706, P < 0.01) and perceived professional identity (r = 0.736, P < 0.01); and resilience was positively correlated with perceived professional identity (r = 0.783, P < 0.01). The total effect coefficient, direct effect coefficient, and indirect effect coefficient of workplace violence and perceived professional identity are “−0.493”, “−0.067”, and “−0.426”, respectively; the indirect effect accounts for 86.41% of the total effect. Among the indirect effects, the specific mediating effects of perceived organizational support and resilience account for 21.50% and 21.10%, respectively, and the chain mediating effects of perceived organizational support and resilience account for 44.02%. Conclusion Workplace violence not only directly harms the perceived professional identity of emergency nurses but also indirectly affects it through the chain mediation of perceived organizational support and resilience. Nursing managers should establish a multi-level intervention system, including strengthening organizational support and enhancing nurses’ resilience, to improve the perceived professional identity of emergency nurses. Clinical trial number Not applicable.